Sleep factors affecting mental health: mechanics and trigger factors - Sexton-Radek, Kathy (Frontiers in Sleep, 2025)
This article explores the concepts in sleep medicine associated with mental health symptoms. A brief overview of key sleep factors is stated, followed by a presentation of empirical research findings on how poor sleep influences mental health conditions. Some specific information on mental health conditions like insomnia, depression, and schizophrenia symptoms are provided. Tables and figures present common sleep conditions associated with mental health conditions. Additionally, a figure by the author proposes a pathway explaining the link between poor sleep quality and mental health conditions.